El bullying y el desarrollo de las habilidades sociales de los estudiantes de la I.E. José María Arguedas - distrito El Porvenir, Trujillo, 2018. - Santa Cruz García, Leila Melissa (2019)
This research is of a correlational type and was carried out with the purpose of identifying how bullying influences the development of social skills (assertive communication, empathy and conflict resolution) of students in the second grade “B” of the secondary level of EI José María Arguedas of the El Porvenir District - Trujillo, 2018; whose sample was conformed by 24 students of the second grade “B” of the secondary level of the I.E. José María Arguedas. The methods used were: Inductive, deductive, analytical and statistical; As for the techniques, observation, interview, literature review and survey were used. To obtain the results, two instruments were applied that allowed us to measure the variables of Bullying (Bullying Questionnaire) and Social Skills (the scale of social skills of A. Goldstein & Col. 1978) separately to then make the respective relationship and discussion of the results obtained, where it is demonstrated that the existence of bullying within the research group promotes the poor practice of assertive communication in students, since only 40.8% communicate assertively with their peers, while 59.2% They do not, in addition, promote the poor practice of empathy in students, since only 44.3% adequately resolve a conflict, while 55.7% do not; as well as, it promotes the low capacity to resolve conflicts in students, since only 39.8% of students are empathic with their peers, while 60.2% are not.